Orbital resonances of Taiwan's FORMOSAT-2 remote sensing satellite - Lin, Shin-Fa; Hwang, Cheinway (My University, 2018)
Unlike a typical remote sensing satellite that has a global coverage and non-integral orbital revolutions per day, Taiwan's FORMOSAT-2 (FS-2) satellite has a non-global coverage due to the mission requirements of one-day repeat cycle and daily visit around Taiwan. These orbital characteristics result in an integer number of revolutions a day and orbital resonances caused by certain components of the Earth's gravity field. Orbital flight data indicated amplified variations in the amplitudes of FS-2's Keplerian elements. We use twelve years of orbital observations and maneuver data to analyze the cause of the resonances and explain the differences between the simulated (at the pre-launch stage) and real orbits of FS-2. The differences are quantified using orbital perturbation theories that describe secular and long-period orbital evolutions caused by resonances. The resonance induced orbital rising rate of FS-2 reaches +1.425 m/day, due to the combined (modeled) effect of resonances and atmospheric drags (the relative modeling errors < 10%). The concave shapes in the time-evolution of the longitude of descending node (LonDN) coincide with the positive rates of daily semi-major axis (SMA) change, also caused by resonances. The non-zonal geopotential coefficients causing the resonance effects contributed up to 45% of FS-2's inclination decline. Our retrospective analysis of FS-2's resonant orbit can provide lessons for a remote sensing mission similar to FS-2, especially in the early mission design and planning phase.
Keywords: FORMOSAT-2 (FS-2); Geopotential coefficient; Longitude of descending node (LonDN); Resonance; Semi-major axis (SMA)